The quality of banking services and its effect on the satisfaction of pilgrims and Umrah performers – A field study on banks in the Kingdom of Saudi Arabia – - Mutair, Ali Abdulaziz Ali; Baqader, Saleh (Journal of Economic, Administrative and Legal Sciences, 2022)
The study aimed to examine the impact of the quality of banking services provided by the Saudi banks on the satisfaction of pilgrims and Umrah performers. To achieve the objectives of the study, the researchers employed descriptive analytical method. The study population represents the bank's clients operating in the Kingdom of Saudi Arabia, where they were chosen randomly, and their number is. (150) clients. The results of the statistical analysis showed that there is a relationship between the dimensions of the quality of banking services and the satisfaction of pilgrims and Umrah performers, and the results showed that the variables affecting the satisfaction of pilgrims and Umrah performers are: responding, compassion, while it was found that there was no effect for the rest of the variables "tangible, reliability, and safety". The study recommended that banks should provide convenient car parking, as well as to increase the level of quality of services provided to the pilgrims and Umrah performers.
Keywords: quality of banking services; satisfaction of pilgrims and Umrah performers; bank